Flexible conductive hydrogel as well as preparation method and application thereof

Through polyacid-induced PEDOT:PSS phase separation and annealing resolvent method, the problem of filling hydrogel composite and insufficient mechanical properties of intrinsic hydrogels were solved, and flexible conductive water with high conductivity and high tensile properties was prepared. Gel realizes effective shielding of electromagnetic waves and meets the application needs of flexible electronic devices and wearable devices.

CN119241990AActive Publication Date: 2025-01-03DONGHUA UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411152614.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-21
Publication Date
2025-01-03
Estimated Expiration
2044-08-21

AI Technical Summary

Technical Problem

The uniform recombination of existing filler conductive hydrogels in inorganic conductive fillers and flexible polymer matrix is ​​difficult to achieve, and the mechanical properties of intrinsic conductive polymer-based hydrogels are poor, which cannot meet the height of flexible electronic devices and wearable devices. Conductivity and tensile requirements.

Method used

Poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid PEDOT:PSS phase separation was induced by polyacid, and flexible conductive hydrogel was prepared by annealing resolvent method. The non-conductive PSS was removed by polyacid, forming a Continuous conductive network, increasing electrical conductivity, and improving mechanical properties by adding polyvinyl alcohol.

Benefits of technology

The prepared hydrogel has high conductivity and excellent electromagnetic shielding performance, with a maximum elongation of break of 96.9%. The total specific electromagnetic shielding performance in the X, Ku and K bands reaches 104.74dB/mm and 104.74dB/mm. and 127.52dB/mm, the shielding performance is mainly absorbed, effectively reducing the secondary pollution of electromagnetic waves.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241990A_ABST
    Figure CN119241990A_ABST
Patent Text Reader

Abstract

The invention relates to flexible conductive hydrogel as well as a preparation method and application thereof, PEDOT: PSS phase separation is induced by polyacid, and the flexible conductive hydrogel is prepared by an annealing complex solvent method. The hydrogel provided by the invention shows excellent electromagnetic shielding effectiveness in X, Ku and K wave bands, is excellent in mechanical tensile property, and has a wide application prospect in the fields of wearable, flexible electronic communication and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of electromagnetic wave shielding materials, and particularly relates to a flexible conductive hydrogel and a preparation method and application thereof. Background Art

[0002] The rapid development of electronic communication technology has brought convenience to people, but it has also brought serious electromagnetic radiation, which not only affects the normal operation of electronic equipment, but also causes harm to human health. The development of high-performance anti-electromagnetic interference materials has become one of the most effective ways to alleviate the increasingly serious electromagnetic pollution problem. Electromagnetic shielding materials, with their high conductivity and strong loss characteristics, can effectively reflect and absorb incident electromagnetic waves, thereby achieving attenuation of electromagnetic waves and reducing their penetration ability. This feature not only effectively protects electronic components exposed to electromagnetic radiation from interference and attack; it also improves the anti-electromagnetic interference and electronic strike capabilities of electronic equipment, and enhances the electromagnetic compatibility of equipment, which is of great significance to the safety of communication systems, human health and environmental protection. In recent years, with the rapid development of portable devices and wearable electronic products, traditional rigid electromagnetic shielding materials can no longer meet application requirements. In response to the characteristics of flexible devices such as bendability, stretchability and compressibility, it is urgent to develop flexible electromagnetic protection materials with high shielding effectiveness.

[0003] Hydrogel is a three-dimensional network structure formed by physical or chemical crosslinking of polymer chains. Its good flexibility and processability have attracted widespread attention in the fields of medicine, environmental science, flexible electronics, etc. Among them, conductive hydrogels with high electron transmission properties can effectively enhance conductivity loss and reflect electromagnetic waves on the surface of the material, thereby effectively reducing the impact of electromagnetic radiation on the environment and human body. It is an electromagnetic shielding material for flexible electronic devices with great application prospects. Conductive hydrogels are generally divided into filled type and intrinsic conductive type. The preparation method of filled conductive hydrogel is to add inorganic conductive fillers to the insulating polymer substrate to improve the conductivity of the hydrogel. Common conductive fillers include graphene oxide, carbon nanotubes, MXene nanosheets and silver nanowires. For example, Yu et al. prepared an organic hydrogel containing MXene nanosheets, whose conductivity was 0.442S / m and electromagnetic shielding effectiveness was as high as 37dB (Yu Y, et al. Nano-Micro Letters, 2022, 14(1): 77.). Although inorganic conductive fillers can effectively improve conductivity, their dispersibility deteriorates during the long polymerization process, and they are prone to aggregation or restacking, resulting in reduced mechanical properties of organic hydrogels. Intrinsic conductive hydrogels are hydrogels prepared directly with conductive polymers as the matrix. Wang et al. used PEDOT:PSS as the matrix and prepared conductive hydrogels doped with ionic liquids by dry annealing and rehydration. The conductivity was as high as 305S / cm and the electromagnetic shielding effectiveness was 54dB. Anions in ionic liquids can partially replace PSS, causing nanophase separation of PEDOT:PSS, thereby improving conductivity (Wang J, et al. Advanced Materials, 2022, 34 (12): 2109904.). However, the maximum strain of the hydrogel is only about 30%, which is not enough to meet the mechanical properties requirements of flexible devices. Therefore, there is an urgent need to develop electromagnetic shielding hydrogels with both high conductivity and good stretchability to meet the application needs of flexible electronic devices and wearable devices in the field of anti-electromagnetic interference. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a flexible conductive hydrogel and a preparation method and application thereof, which solves the problem that inorganic conductive fillers and flexible polymer matrices are difficult to be uniformly compounded in the current filled conductive hydrogel, as well as the problem that the mechanical properties of intrinsic conductive polymer-based hydrogels are poor.

[0005] The invention provides a flexible conductive hydrogel, which is prepared by an annealing and resolvation method by using a polyacid to induce poly(3,4-ethylenedioxythiophene)-polystyrene sulfonate PEDOT:PSS phase separation.

[0006] Preferably, the polyacid is phosphotungstic acid.

[0007] The present invention also provides a method for preparing a flexible conductive hydrogel, comprising the following steps:

[0008] (1) dissolving a polyacid in a solvent by ultrasonic dispersion to obtain a polyacid solution; then adding a resin to the polyacid solution, heating it in an oil bath and condensing and refluxing it to fully disperse the resin in the polyacid solution; and finally cooling the mixed solution to room temperature for later use;

[0009] (2) The mixed solution obtained in step (1) is mixed with PEDOT:PSS to form a pre-gel, annealed at 90-95° C. for 2-6 hours, and a solvent is added to obtain a flexible conductive hydrogel.

[0010] Preferably, the concentration of the polyacid solution in step (1) is 0.1-0.3 mol / L.

[0011] Preferably, the resin in step (1) is polyvinyl alcohol; the mass fraction of the resin in the mixed solution is 6%-12%.

[0012] Preferably, the ultrasonic time in step (1) is 10-20 min.

[0013] Preferably, the oil bath heating temperature in step (1) is 95° C. and the heating time is 2 h.

[0014] Preferably, the volume ratio of the mixed solution to the conductive polymer in step (2) is 1:3.

[0015] Preferably, the solvent in step (1) is a mixed solvent of water and glycerol in a volume ratio of 1:0.1-1.

[0016] Preferably, the solvent in step (2) is a mixed solvent of water and glycerol in a volume ratio of 1:0-1.

[0017] The invention also provides an application of a flexible conductive hydrogel in the fields of microwave darkroom, military stealth and electromagnetic protection.

[0018] Beneficial Effects

[0019] (1) The present invention uses polyacid to induce PEDOT:PSS phase separation, and prepares a conductive hydrogel that can effectively shield multi-band electromagnetic waves by annealing and resolventization. The polyacid can partially remove the non-conductive PSS in the conductive polymer PEDOT:PSS, effectively increasing the conductivity of the hydrogel. Compared with the traditional hydrogel preparation process, this method has a shorter preparation cycle and a simpler process flow.

[0020] (2) The hydrogel prepared by the present invention has a unique microstructure, and the polyacid induces PEDOT:PSS to form a continuous conductive network, thereby enhancing the conductivity loss and allowing the incident electromagnetic wave to be quickly dissipated in the form of heat energy. In addition, the abundant polar water molecules, glycerol and polyacid in the hydrogel provide abundant polarization centers, which are beneficial to dipole polarization and greatly improve the electromagnetic shielding performance of the composite material. The hydrogel prepared by the present invention has excellent electromagnetic shielding effectiveness, and the total specific electromagnetic shielding effectiveness (SSET) in the X, Ku and K bands can reach 104.74dB / mm, 104.74dB / mm and 127.52dB / mm respectively, and the shielding performance is mainly absorption, which effectively reduces the secondary pollution of electromagnetic waves.

[0021] (3) The present invention uses polyvinyl alcohol as an additive, which effectively improves the mechanical properties and environmental stability of the hydrogel and develops a flexible electromagnetic shielding hydrogel for practical applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is the SEM image of the PWP0 flexible conductive hydrogel prepared in Example 1.

[0023] Figure 2 The X-band SSE of the PWP0 flexible conductive hydrogel prepared in Example 1 T , SSE A and SSE R Test results.

[0024] Figure 3 The PWP0 flexible conductive hydrogel prepared in Example 1 is SSE in the Ku band T , SSE A and SSE R Test results.

[0025] Figure 4 This is the stress-strain curve of the PWP0 flexible conductive hydrogel obtained in Example 1.

[0026] Figure 5 The X-band SSE of PWP20 flexible conductive hydrogel prepared in Example 2 T , SSE A and SSE R Test results.

[0027] Figure 6 The PWP20 flexible conductive hydrogel prepared in Example 2 is SSE in the Ku band T , SSE A and SSE R Test results.

[0028] Figure 7This is the stress-strain curve of the PWP20 flexible conductive hydrogel obtained in Example 2.

[0029] Figure 8 The X-band SSE of PWP60 flexible conductive hydrogel prepared in Example 3 T , SSE A and SSE R Test results.

[0030] Fig. 9 The PWP60 flexible conductive hydrogel prepared in Example 3 is SSE in the Ku band T , SSE A and SSE R Test results.

[0031] Fig.10 The K-band SSE of PWP60 flexible conductive hydrogel prepared in Example 3 T , SSE A and SSE R Test results.

[0032] Fig.11 This is the stress-strain curve of the PWP60 flexible conductive hydrogel obtained in Example 3.

[0033] Fig.12 The PWP100 flexible conductive hydrogel prepared in Example 4 is SSE in the X-band T , SSE A and SSE R Test results.

[0034] Fig.13 The PWP100 flexible conductive hydrogel prepared in Example 4 is SSE in the Ku band T , SSE A and SSE R Test results.

[0035] Fig.14 This is the stress-strain curve of the PWP100 flexible conductive hydrogel prepared in Example 4. DETAILED DESCRIPTION

[0036] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0037] Example 1

[0038] (1) Weigh 4.725 g (0.15 mol / L) of phosphotungstic acid (hereinafter referred to as PW 12 ) and 1g polyvinyl alcohol (PVA) were dissolved in 5ml H 2 O and 5 ml of glycerol in a mixed aqueous solution, stirred at 95 ° C for 2 h to form PW 12 / PVA aqueous solution.

[0039] (2) Then, it was mixed with PEDOT:PSS aqueous dispersion in a volume ratio of 1:3 and stirred for 2 min at room temperature to form a pre-gel. After sealing, it was annealed at 90°C for 2.5 h and then immersed in water to obtain a flexible conductive hydrogel. Test results: The morphology of the hydrogel prepared in this example was characterized by a scanning electron microscope (SU8010, Hitachi, Japan). Figure 1 As shown, polyacids induce the formation of a unique three-dimensional network structure inside PEDOT:PSS hydrogel.

[0040] The hydrogel prepared in this example was cut into rectangular samples with length × width of 22.9 mm × 10.2 mm and 15.9 mm × 8.03 mm with unlimited thickness using a mold, and the shielding performance of the samples in the range of 8.2-12.4 GHz and 12.4-18 GHz was tested by a vector network analyzer (Keysight, N5234B). Figure 2 , 3 As shown, the concentration of PVA / PW is 0.15 mol / L 12 / The total specific electromagnetic shielding effectiveness SSE of PEDOT-GLY 0% hydrogel (PWP0 for short) in the 8.2-12.4GHz band T =58.42dB / mm, where SSE A =48.27dB / mm, SSE R =10.15dB / mm; Total specific electromagnetic shielding effectiveness SSE in the 12.4-18GHz band T =55.55dB / mm, where SSE A =46.43dB / mm, SSE R =9.12dB / mm.

[0041] The conductivity of the hydrogel prepared in this example was measured using the four-probe method and the PWP0 was 14.07 S / cm.

[0042] The stress-strain curve of the hydrogel prepared in this example was tested by an electronic universal material testing machine (INSTRON / 5969). Figure 4 As shown, the maximum elongation at break of PWP0 is 33.2% and the Young's modulus is 0.12 MPa.

[0043] Example 2

[0044] The difference between this embodiment and embodiment 1 is that after annealing, it is immersed in a 20% glycerol aqueous solution, and the rest is the same as embodiment 1.

[0045] Test results: The hydrogel prepared in this example was cut into rectangular samples with length × width of 22.9 mm × 10.2 mm and 15.9 mm × 8.03 mm with unlimited thickness using a mold, and the shielding performance of the samples in the range of 8.2-12.4 GHz and 12.4-18 GHz was tested by a vector network analyzer (Keysight, N5234B). Figure 5 , 6 As shown, the concentration of PVA / PW is 0.15 mol / L 12 Total specific electromagnetic shielding effectiveness (SSE) of PEDOT-GLY 20% (PWP20) hydrogel in the 8.2-12.4 GHz band T =80.88dB / mm, where SSE A =68.59dB / mm, SSE R =12.29dB / mm; Total specific electromagnetic shielding effectiveness SSE in the 12.4-18GHz band T =72.08dB / mm, where SSE A =61.72dB / mm, SSE R =10.36dB / mm.

[0046] The conductivity of the hydrogel prepared in this example was measured using a four-probe method and the conductivity of PWP20 was 3.75 S / cm.

[0047] The stress-strain curve of the hydrogel prepared in this example was tested by an electronic universal material testing machine (INSTRON / 5969).

[0048] like Figure 7 As shown, the maximum elongation at break of PWP20 is 68.3% and the Young's modulus is 0.12 MPa.

[0049] Example 3

[0050] The difference between this embodiment and embodiment 1 is that after annealing, it is immersed in a 60% glycerol aqueous solution, and the rest is the same as embodiment 1.

[0051] Test results: The hydrogel prepared in this example was cut into rectangular samples with length × width of 22.9 mm × 10.2 mm, 15.9 mm × 8.03 mm and 10.95 mm × 4.5 mm respectively using a mold, and the shielding performance of the samples in the range of 8.2-12.4 GHz, 12.4-18 GHz and 18-26.5 GHz was tested by a vector network analyzer (Keysight, N5234B). Figure 8 , 9 , 10, the concentration of PVA / PW is 0.15 mol / L 12 The total specific electromagnetic shielding effectiveness SSET of PEDOT-GLY 60% (PWP60 for short) hydrogel in the 8.2-12.4 GHz band is 105.31 dB / mm, where SSE A =86.01dB / mm, SSE R =19.30dB / mm; Total specific electromagnetic shielding effectiveness SSE in the 12.4-18GHz band T =104.10dB / mm, where SSE A =86.48dB / mm, SSE R =17.62dB / mm; Total specific electromagnetic shielding effectiveness SSE in the 18-26.5GHz band T =129.52dB / mm, where SSE A =116.17dB / mm, SSE R =13.35dB / mm.

[0052] The conductivity of the hydrogel prepared in this example was measured using a four-probe method and the conductivity of PWP60 was 15.65 S / cm.

[0053] The stress-strain curve of the hydrogel prepared in this example was tested by an electronic universal material testing machine (INSTRON / 5969). Fig.11 As shown, the maximum elongation at break of PWP60 is 96.9% and the Young's modulus is 0.43 MPa.

[0054] Example 4

[0055] The difference between this embodiment and embodiment 1 is that after annealing, it is immersed in a 100% glycerol aqueous solution, and the rest is the same as embodiment 1.

[0056] Test results: The hydrogel prepared in this example was cut into rectangular samples with length × width of 22.9 mm × 10.2 mm and 15.9 mm × 8.03 mm with unlimited thickness using a mold, and the shielding performance of the samples in the range of 8.2-12.4 GHz and 12.4-18 GHz was tested by a vector network analyzer (Keysight, N5234B). Fig.12 , 13 As shown, the concentration of PVA / PW is 0.15 mol / L 12 Total specific electromagnetic shielding effectiveness (SSE) of PEDOT-GLY 100% (PWP100) hydrogel in the 8.2-12.4 GHz band T =93.15dB / mm, where SSE A =74.93dB / mm, SSE R =18.22dB / mm; Total specific electromagnetic shielding effectiveness SSE in the 12.4-18GHz band T =93.15dB / mm, where SSE A =81.03dB / mm, SSE R =12.12dB / mm.

[0057] The conductivity of the hydrogel prepared in this example was measured by the four-probe method and the conductivity of PWP100 was 2.61 S / cm.

[0058] The stress-strain curve of the hydrogel prepared in this example was tested by an electronic universal material testing machine (INSTRON / 5969). Fig.14 As shown, the maximum elongation at break of PWP100 is 64.6% and the Young's modulus is 0.99 MPa.

[0059] The above embodiments are only preferred embodiments of the present invention and are not any formal or substantial limitations of the present invention. It should be pointed out that ordinary technicians in this technical field can make several improvements and supplements without departing from the present invention, and these improvements and supplements should also be regarded as the scope of protection of the present invention.

Claims

1. A flexible conductive hydrogel, characterized in that: Poly(3,4-ethylenedioxythiophene)-polystyrene sulfonate PEDOT:PSS was prepared by annealing and resolventization method using polyacid-induced phase separation.

2. The flexible conductive hydrogel according to claim 1, characterized in that: The polyacid is phosphotungstic acid.

3. A method for preparing the flexible conductive hydrogel according to any one of claims 1 to 2, comprising the following steps: (1) dissolving a polyacid in a solvent by ultrasonic dispersion to obtain a polyacid solution; then adding a resin to the polyacid solution, heating it in an oil bath and condensing and refluxing it to fully disperse the resin in the polyacid solution; and finally cooling the mixed solution to room temperature for later use; (2) The mixed solution obtained in step (1) is mixed with PEDOT:PSS to form a pre-gel, annealed at 90-95° C. for 2-6 hours, and a solvent is added to obtain a flexible conductive hydrogel.

4. The preparation method according to claim 3, characterized in that: The concentration of the polyacid solution in step (1) is 0.1-0.3 mol / L.

5. The preparation method according to claim 3, characterized in that: The resin in step (1) is polyvinyl alcohol; the mass fraction of the resin in the mixed solution is 6%-12%.

6. The preparation method according to claim 3, characterized in that: The ultrasonic time in step (1) is 10-20 min.

7. The preparation method according to claim 3, characterized in that: The solvent in step (1) is a mixed solvent of water and glycerol in a volume ratio of 1:0.1-1.

8. The preparation method according to claim 3, characterized in that: The solvent in step (2) is a mixed solvent of water and glycerol in a volume ratio of 1:0-1.

9. The preparation method according to claim 3, characterized in that: The volume ratio of the mixed solution to the conductive polymer in the step (2) is 1:

3.

10. Use of the flexible conductive hydrogel according to any one of claims 1 to 2 in the fields of microwave darkroom, military stealth and electromagnetic protection.

Citation Information

Patent Citations

  • Polyvinyl alcohol-based conductive hydrogel and preparation method and application thereof

    CN110240714A

  • Super-soft conductive self-healing hydrogel as well as preparation method and application thereof

    CN112679753A

  • Method for preparing hydrogel electrolyte with wide voltage window through polyacid regulation

    CN115938816A

  • Hybrid conductive polymer dispersion system as well as preparation method and application thereof

    CN118185003A

  • System for inspecting steel scrap video based on artificial intelligence

    KR1020250177621A